The concept of resilience: a bibliometric analysis of the emergency and disaster management literature. Issue 3 (4th May 2019) - Demiroz, Fatih; Haase, Thomas W.
ABSTRACT: Resilience has become an important concept in the fields of emergency and disaster management. Despite the increased use of resilience in the academic and public policy arenas, the intellectual topography of this subject as it relates to emergency and disaster management contexts remains under-investigated. This article provides a snapshot of the intellectual structure of resilience studies. Using bibliometric data collected from 20 emergency and disaster management journals, this article argues that the interdisciplinary nature of resilience research comes from its historical roots. The findings also demonstrate that resilience research in the emergency and disaster management fields is organised into three primary clusters: environmental and ecological issues, emergency and disaster management, and public policy and administration. The article concludes with implications for policymakers, as well as recommendations for future research.